Marketing Innovation’s Reality in Tourism Agencies from both Perspectives: Agency and Customers -- ‘‘ELWAFIDINE TOURS Agency Case Study’’. - Amel, CHETRAOUI (Université de M'sila, 2018)
This study investigated the reality of marketing innovation in the tourist agencies from both perspectives: agency and customers, focusing on ‘‘ELWAFIDINE TOURS’’ agency as a case study, by using qualitative and quantitative approaches, and depending on a deep interview and a questionnaire as study tools. The study used open and half closed questions in the frame of deep interview embodiment, and a questionnaire targeting customers of the agency. The study results indicated that the agency adopts innovation in its varied marketing mixture strategies, what is considered one of the main reasons of its competitive superiority
Keywords: Innovation, Marketing Innovation, Tourist Agencies, ‘‘ELWAFIDINE TOURS’’, Marketing Mixture Strategies.